Empirical assessment and comparison of neuro-evolutionary methods for the automatic off-line design of robot swarms - Ken Hasselmann (Nature Portfolio, 2021)
Off-line neuro-evolution produces robot swarms whose good performance in simulation does not often transfer to the real word. With an extensive empirical study, Hasselmann et al. substantiate overfitting as the dominant cause.